Response of crytocoryne ferruginea engler to shading and water depth - Azzlin Arenayati, Hashim (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Study on response of Cryptoeoryne jerruginea Engler on shading and water depth carried out at greenhouse FSTS, Unimas. Plants at tree canopy shading have the highest rate for total leaf area (A), Leaf Weight Ratio (LWR), Leaf Area Ratio (LAR) and Leaf Area Duration (LAD). For 50% shading plants had highest in Stem Weight Ratio (SWR), Root Weight Ratio (RWR), Specific Leaf Area (SLA), Net Assimilation Rate (NAR) and Dry Matter Production (DMP). 75% shading plants had the highest rate for Plant Dry Weight (W). The Plant Dry Weight, SWR and UWR between tree canopy, 50% and 75% shading had no significan t different. The highest values of Total Leaf Area (A), Leaf Weight Ratio (LWR), Rhizome Weight Ratio (UWR) and Leaf Area Duration (LAD) were obtained from 5 cm water depth. Plants at 0 cm water depth had highest in Leaf Weight Ratio (LWR) and Net Assimilation Rates (NAR). Plants at 15 cm water depth showed the highest rate for Root Weight Ratio (RWR), Stem Weight Ratio (SWR), Specific Leaf Area (SLA), Leaf Area Ratio (lAR), Dry Matter Production (DMP) and Net Assimilation Rates (NAR). The W, SWR, UWR, SLA and NAR between 0 cm, 5 cm and 15 cm water depth had no significant different. As for the photosynthesis, plants at 0 cm water depth showed better yield production.